2021
DOI: 10.1002/pip.3527
|View full text |Cite
|
Sign up to set email alerts
|

Importance of atmospheric aerosol pollutants on the degradation of Al2O3 encapsulated Al‐doped zinc oxide window layers in solar cells

Abstract: Atmospheric aerosol pollutants are considered for the first time for the durability evaluation of non-metallic photovoltaic materials on the example of pristine and Al 2 O 3 -encapsulated Al-doped zinc oxide (AZO) window layers. The AZO samples were exposed to a varied temperature and humidity cycle, completed or not by a daily deposition of (NH 4 ) 2 SO 4 or NaCl aerosols, typical pollutants in rural and marine environments, respectively. The samples exposed with and without the pollutants were compared after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 52 publications
(127 reference statements)
3
7
0
Order By: Relevance
“…The XPS results are therefore consistent with the visual observations and with literature 7 that while a 25 nm thick ALD-Al 2 O 3 layer strongly limited the degradation of "No pollutant" samples (subjected only to the variations of temperature and humidity), it was inefficient in the presence of all the tested salts. The XPS results of this work are also consistent with the previous works, demonstrating that a 25 nm thick Al 2 O 3 encapsulation on the AZO windows layers successfully passed the 1000 h DH test11 but degraded in the presence of NaCl or (NH 4 ) 2 SO 4 aerosols and temperature and humidity cycling 7. XPS also confirmed that Mo was mainly present as Mo (VI) oxides (Mo 3d 5/2 binding energies at 232.4 ± 0.1 eV and 233.3 ± 0.1 eV).32 The unexposed SLG/Mo/CIGS/Al 2 O 3 configuration revealed the presence of the Al 2 O 3 encapsulation layer without any detectable signal from the underlying CIGS layer.…”
supporting
confidence: 90%
See 4 more Smart Citations
“…The XPS results are therefore consistent with the visual observations and with literature 7 that while a 25 nm thick ALD-Al 2 O 3 layer strongly limited the degradation of "No pollutant" samples (subjected only to the variations of temperature and humidity), it was inefficient in the presence of all the tested salts. The XPS results of this work are also consistent with the previous works, demonstrating that a 25 nm thick Al 2 O 3 encapsulation on the AZO windows layers successfully passed the 1000 h DH test11 but degraded in the presence of NaCl or (NH 4 ) 2 SO 4 aerosols and temperature and humidity cycling 7. XPS also confirmed that Mo was mainly present as Mo (VI) oxides (Mo 3d 5/2 binding energies at 232.4 ± 0.1 eV and 233.3 ± 0.1 eV).32 The unexposed SLG/Mo/CIGS/Al 2 O 3 configuration revealed the presence of the Al 2 O 3 encapsulation layer without any detectable signal from the underlying CIGS layer.…”
supporting
confidence: 90%
“…According to the literature, the main cause of the efficiency loss of CIGS cells in the presence of humidity can be ascribed to the resistivity increase of the AZO layer 12–14 . Our previous work 7 has also demonstrated that the atmospheric aerosols can crucially decrease the life time of AZO. The combined effect of humidity and atmospheric aerosol pollution on other layers of the CIGS cell, in particular the back contact and absorber, was not reported in the literature to the extent of our knowledge.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations